FORGOTTEN MISSION OF PHYSICAL EDUCATION - Zoran Milošević; Nebojša Maksimović; Radenko Matić; Duško Bjelica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Physical education represents, on an ungrounded basis, one of the last oases of civilization survival of the contemporary man, which is realized within the framework of forced work and "culture" of consumption. Searching for the remaining sense of freedom, physical education is often a compensation for the lost beauty, sociability, and predominantly health. The value of all values in the darkness of overpowering media-consumption induced passivization of potential participants, commercialization of contents, as well as dehumanization of almost all forms of phenomena are characteristics of the time whose "achievements" require new foci and strategies in which even "remembering future" is a step further away from the misfortune of those who do not know what they want and catastrophe of those who do not know what they can. Remembering the outstanding forerunners from the other half of 19th century, especially the present actual proponents of "European values", we can rightly ask ourselves a question "Do we have right to forget the values we used to cultivate, which saved our future".